Química de Todos los Días: Un Mundo de Óxidos - Alfredo Gutiérrez, J. (Acta Universitaria, 2002)
When common people listen the word “oxide” usually they only think of the rust that forms on the surface of some metallic objects, but the term, however, embraces a wide variety of substances. Water, for instance, is a true oxide. Oxides are so many and common that it is hard to believe that these, or some of their derivatives, compose most of the mineral world and in some cases they are vital for life. It is interesting to note that there are two main classes of oxides: acidic and alkaline. These types of oxides are chemical antagonists in such a way that neutralize each other producing salts, some kind of very stable substances. Neutralizing reactions are very important for both the natural world and people’s everyday life.
Keywords: Array; Array; Array; Array; Array